Bariatric Surgery in an Effort to Resolve Obstructive Sleep Apnea - Seerwan Abdullah, Karzan; Twana Mohammed, Ara; Shalaw Jamal, Aland; Hussein Mohammed, Ali (Hammurabi Journal of Medical Sciences, 2026)
Background: Obstructive sleep apnea is correlated with obesity, and of weight loss, as such; it helps improve obstructive sleep apnea. Objectives: This study aims to assess if bariatric surgery as obesity continues to rise worldwide, the prevalence of obstructive sleep apnea is increasing as well. There are many ways to lose weight and among them, bariatric surgery is associated with a significant amount has a role in improving and perhaps resolving obstructive sleep apnea in the long run. Materials and Method: A cross-sectional study composed of quantitative methodology. A total of 143 patients who had previously undergone bariatric surgery were recruited and the data was collected by contacting the participants through the telephone to ask them questions based on an evidence-based questionnaire. Result: The average age of the patients was 36.63 ± 9.71 years and 51 (35.6%) patients were males whereas females accounted for the remaining 92 (64.4%) patients. The most common age group was the 39-48 years group with 54 patients. The average BMI after surgery was 30.28 kg/m2 while before surgery; the average was 44.86 kg/m2. Conclusion: Bariatric surgery is an efficient way of losing weight, especially a weight loss significant enough to resolve OSA. Majority of patients are satisfied with the results of the surgery and consider their first 6-month experience following the surgery a good experience.